2013
DOI: 10.1053/j.gastro.2013.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination With ENO1 DNA Prolongs Survival of Genetically Engineered Mice With Pancreatic Cancer

Abstract: See Covering the Cover synopsis on page 862. BACKGROUND & AIMS:Pancreatic ductal adenocarcinoma (PDA) is an aggressive tumor, and patients typically present with late-stage disease; rates of 5-year survival after pancreaticoduodenectomy are low. Antibodies against ␣-enolase (ENO1), a glycolytic enzyme, are detected in more than 60% of patients with PDA, and ENO1-specific T cells inhibit the growth of human pancreatic xenograft tumors in mice. We investigated whether an ENO1 DNA vaccine elicits antitumor immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 41 publications
7
117
0
Order By: Relevance
“…ENO1-specific T cells spared normal keratinocytes in in vitro cytotoxic assay [20] and no autoimmunity event nor side effects were detected after DNA-vaccination [21] or anti-ENO1 mAb treatment [13] in mice. This suggests that both ENO1-DNA vaccine and anti-ENO1 mAb therapy are safe.…”
Section: Natural Anti-eno1 Antibodies Elicited By Eno1 Vaccinationmentioning
confidence: 95%
See 2 more Smart Citations
“…ENO1-specific T cells spared normal keratinocytes in in vitro cytotoxic assay [20] and no autoimmunity event nor side effects were detected after DNA-vaccination [21] or anti-ENO1 mAb treatment [13] in mice. This suggests that both ENO1-DNA vaccine and anti-ENO1 mAb therapy are safe.…”
Section: Natural Anti-eno1 Antibodies Elicited By Eno1 Vaccinationmentioning
confidence: 95%
“…This prompted us to propose ENO1 as a therapeutic candidate owing to its ability to induce an integrated humoral and cellular response. We developed a DNA vaccination to ENO1 in genetically engineered mice (GEM) that spontaneously develop autochthonous, lethal pancreatic cancer [21], and we showed that the vaccine significantly induced a specific immune response against pancreatic tumors, which efficiently prolonged mouse survival. We demonstrated that ENO1 DNA vaccination induced a specific antibody as well as a cellular response in mice.…”
Section: Natural Anti-eno1 Antibodies Elicited By Eno1 Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of clinical relevance, the therapeutic efficacy of the ENO1 DNA vaccine was observed to be very promising when the administration protocol started at 8 months to 9 months of age. 107 In these mice, the ENO1 DNA vaccine also induced the formation of intratumoral tertiary lymphoid tissue (TLT) with active germinal centers and correlated with increased recruitment of T-cells. 108 Analysis of human PDA tissues by immunohistochemistry revealed two distinct patterns of B-cell distribution, either as randomly infiltrating cells (CD20-tumor-infiltrating …”
Section: Passive Immunotherapy Combined With Antitumor Vaccinesmentioning
confidence: 99%
“…DNA-based vaccination against human ENOA is able to significantly prolong the median life expectancy of mice that spontaneously develop PDAC, by inducing both a humoral and cellular response [27].…”
mentioning
confidence: 99%